ANALISIS PERBEDAAN ANTARA PEMBELAJARAN GALLERY WALK DAN THINK PAIR SHARE DENGAN MEDIA POSTER UNTUK MENINGKATKAN PENGUASAAN KETERAMPILAN KOGNITIF MATERI EKONOMI SUMBER DAYA MANUSIA DAN KETENAGAKERJAAN MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS PGRI JOMBANG - Putri Pertama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to compare the effectiveness of the Gallery Walk and Think Pair Share (TPS) learning models, both supported by poster media, in improving students’ cognitive skills in the Human Resource Economics and Employment course. A quasi-experimental design with two experimental groups was employed. The participants consisted of 40 students of the Economic Education Study Program at Universitas PGRI Jombang, divided equally into a Gallery Walk class and a Think Pair Share class. Data were collected through pretests, posttests, and student response questionnaires. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, and the Mann–Whitney U test. The findings revealed that the Gallery Walk group achieved a higher mean posttest score (82.75) than the Think Pair Share group (71.75). The Mann–Whitney U test showed a significance value of 0.027 (p < 0.05), indicating a statistically significant difference in students’ cognitive skills between the two learning models. Student responses toward both learning models were categorized as good, with percentage scores of 73.88% for Gallery Walk and 76.63% for Think Pair Share. These findings indicate that both learning models positively support the learning process; however, Gallery Walk assisted by poster media is more effective in improving students’ cognitive skills than Think Pair Share assisted by poster media. Therefore, the Gallery Walk model can be considered an effective alternative learning strategy for enhancing cognitive learning outcomes in higher education economics courses.